2022
DOI: 10.3390/ijms23158782
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Cd38-Cyclic ADP-Ribose Signaling in Cardiomyocytes by Intermittent Hypoxia via Pten Upregulation

Abstract: Sleep apnea syndrome (SAS) is characterized by recurrent episodes of oxygen desaturation and reoxygenation (intermittent hypoxia, IH), and it is a risk factor for cardiovascular disease (CVD) and insulin resistance/type 2 diabetes. However, the mechanisms linking IH stress and CVD remain elusive. We exposed rat H9c2 and mouse P19.CL6 cardiomyocytes to experimental IH or normoxia for 24 h to analyze the mRNA expression of the components of Cd38-cyclic ADP-ribose (cADPR) signaling. We found that the mRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…The cells were kept at 37 °C, 5% CO 2 , and 95% humidity, and the medium was changed every day. Cells were exposed to either normoxia (21% O 2 , 5% CO 2 , and balanced N 2 ), intermittent hypoxia (IH: 70 cycles of 5 min sustained hypoxia [1% O 2 , 5% CO 2 , and balanced N 2 ] and 10 min normoxia), or sustained hypoxia (1% O 2 , 5% CO 2 , and balanced N 2 ) using a custom-designed, computer-controlled incubation chamber attached to an external O 2 -CO 2 -N 2 computer-driven controller (O 2 programmable control, 9200EX, Wakenbtech CO., Ltd., Kyoto, Japan), as described [ 3 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. These conditions are similar to the conditions reported in patients with severe degrees of SAS: in severe cases of SAS, patients are repeatedly exposed to severe hypoxemia followed by mild hypoxemia or normoxia (i.e., IH).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were kept at 37 °C, 5% CO 2 , and 95% humidity, and the medium was changed every day. Cells were exposed to either normoxia (21% O 2 , 5% CO 2 , and balanced N 2 ), intermittent hypoxia (IH: 70 cycles of 5 min sustained hypoxia [1% O 2 , 5% CO 2 , and balanced N 2 ] and 10 min normoxia), or sustained hypoxia (1% O 2 , 5% CO 2 , and balanced N 2 ) using a custom-designed, computer-controlled incubation chamber attached to an external O 2 -CO 2 -N 2 computer-driven controller (O 2 programmable control, 9200EX, Wakenbtech CO., Ltd., Kyoto, Japan), as described [ 3 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. These conditions are similar to the conditions reported in patients with severe degrees of SAS: in severe cases of SAS, patients are repeatedly exposed to severe hypoxemia followed by mild hypoxemia or normoxia (i.e., IH).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated using an RNeasy plus mini kit (Qiagen, Hilden, Germany) from H9c2 and P19.CL6 cells, and cDNA was synthesized from total RNA as a template using a High Capacity cDNA Reverse Transcription kit (Applied Biosystems, Foster City, CA, USA), as described [ 73 , 74 , 75 , 79 , 82 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. Real-time PCR was performed using SYBR ® Fast qPCR kit (KAPA Biosystems, Boston, MA, USA) and a Thermal Cycler Dice Real Time System (Takara Bio, Kusatsu, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the expression of phosphatase and tensin homolog deleted from chromosome 10 (Pten) was upregulated by IH stimulation. The introduction of siRNA into Pten abolished the IH-induced reduction of Cd38, Ryr2, and Fkbp12.6 [ 113 ]. We treated H9c2 rat cardiomyocytes with 3-deaza-cADPR, a cell-permeable cADPR agonist [ 114 ], and introduced it into the cardiomyocyte culture medium, and found that the IH-induced decreases in Cd38, Ryr2, and Fkbp12.6 were attenuated, indicating that IH indeed reduces Cd38 expression, Cd38 activity (ADP-ribosyl cyclase activity for cADPR synthesis), and cADPR concentration in cardiomyocytes.…”
Section: The Effect Of Ih On Blood Pressure Regulationmentioning
confidence: 99%